2013
DOI: 10.1016/j.ahj.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors associated with failure to attain low-density lipoprotein cholesterol goal at 6 months after acute myocardial infarction

Abstract: Background Although controversial, reducing low-density lipoprotein cholesterol (LDL-C) to target levels remains a common therapeutic goal after acute myocardial infarction (AMI). We sought to illuminate patient and provider characteristics associated with LDL-C goal nonattainment after AMI. Methods In an observational registry of 24 United States hospitals, we included 366 AMI patients who had baseline LDL-C levels ≥100 mg/dl and underwent 6-month fasting LDL-C reassessment. Our primary outcome was failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(17 reference statements)
0
17
1
Order By: Relevance
“…European guidelines [23] recommend that TG-targeting treatment should be started when TG levels are >1.7 mmol/L in high-risk CAD patients. Diabetes mellitus is often combined with hypertriglyceridemia [25,26] and some studies showed that the rates of achieving the LDL-C goal was lower in ACS patients with diabetes mellitus combined with hypertriglyceridemia, [27] but the present study and a recent study [22] did not reach this conclusion. Additional studies are necessary to clarify these points.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…European guidelines [23] recommend that TG-targeting treatment should be started when TG levels are >1.7 mmol/L in high-risk CAD patients. Diabetes mellitus is often combined with hypertriglyceridemia [25,26] and some studies showed that the rates of achieving the LDL-C goal was lower in ACS patients with diabetes mellitus combined with hypertriglyceridemia, [27] but the present study and a recent study [22] did not reach this conclusion. Additional studies are necessary to clarify these points.…”
Section: Discussioncontrasting
confidence: 88%
“…[25,26] Indeed, previous studies showed that target achievement was associated with compliance and that compliance was associated with a higher number of follow-up visits. [25,26] TG levels in patients who did not reach the LDL-C goal were higher than those in patients who reached the goal ( P  < 0.001). European guidelines [23] recommend that TG-targeting treatment should be started when TG levels are >1.7 mmol/L in high-risk CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are the standard of care, supported by a large body of data demonstrating robust effectiveness in lowering LDL-C and in reducing the risk for cardiovascular disease (1,2). However, many individuals at risk for cardiovascular disease fail to achieve LDL-C goals (3,4). Only a relatively few number of alternative, nonstatin agents have been approved for lowering LDL-C levels, and their LDL-C-lowering efficacy is modest.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, failure to achieve an optimal reduction of lipid levels can often be observed in real life. Martin et al (2013) recently noted that patients with acute myocardial infarction (AMI) often failed to reach the target level of low-density lipoprotein (LDL)-cholesterol <100 mg/dL at 6-month follow-ups after discharge from the hospital. Among their 336 AMI patients, 33% (n = 121 patients) did not attain the lipid levels goal, and this was due to the absence of statin therapy prescription at discharge, reduced adherence to therapy, lack of cardiac rehabilitation participation and/or diet/activity counselling.…”
Section: Introductionmentioning
confidence: 99%